Simultaneous Relationship between Financial Inclusion, Economic Growth, and Income Inequality in Sulawesi Island, 2011-2019 - Nursaliyawati, Adella Siti; Oktora, Siskarossa Ika (Economics and Finance in Indonesia, 2022)
Sulawesi Island has fairly high economic growth but is not followed by a significant decrease in income inequality. Therefore, a new strategy is needed to overcome these problems, one of them by increasing the role of the financial sector through financial inclusion. This study aims to analyze the relationship between financial inclusion, economic growth, and income inequality, as well as the factors influencing them in Sulawesi Island from 2011 to 2019. The analytical method used is the simultaneous equation model with panel data using the EC2SLS model. The results show that there is a simultaneous relationship between financial inclusion and economic growth and also between economic growth and income inequality. Economic growth has a positive and significant effect on financial inclusion. Financial inclusion, foreign direct investment, and government spending have a positive and significant effect, while income inequality has a negative and significant effect on economic growth. Financial inclusion and inflation have a positive and significant effect, while economic growth has a negative and significant effect on income inequality. Thus, this study can show that financial inclusion can reduce income inequality by promoting economic growth.